Fiber intake and total and cause-specific mortality in the European Prospective Investigation into Cancer and Nutrition cohort. - Chuang, S; Norat, T; Murphy, N; Olsen, A; Tjønneland, A; Overvad, K; Boutron-Ruault, M; Perquier, F; Dartois, L; Kaaks, R; Teucher, B; Bergmann, M; et al. (2012)
BACKGROUND: Previous studies have shown that high fiber intake is associated with lower mortality. However, little is known about the association of dietary fiber with specific causes of death other than cardiovascular disease (CVD). OBJECTIVE: The aim of this study was to assess the relation between fiber intake, mortality, and cause-specific mortality in a large European prospective study of 452,717 men and women. DESIGN: HRs and 95% CIs were estimated by using Cox proportional hazards models, stratified by age, sex, and center and adjusted for education, smoking, alcohol consumption, BMI, physical activity, total energy intake, and, in women, ever use of menopausal hormone therapy. RESULTS: During a mean follow-up of 12.7 y, a total of 23,582 deaths were recorded. Fiber intake was inversely associated with total mortality (HR(per 10-g/d increase): 0.90; 95% CI: 0.88, 0.92); with mortality from circulatory (HR(per 10-g/d increase): 0.90 and 0.88 for men and women, respectively), digestive (HR: 0.61 and 0.64), respiratory (HR: 0.77 and 0.62), and non-CVD noncancer inflammatory (HR: 0.85 and 0.80) diseases; and with smoking-related cancers (HR: 0.86 and 0.89) but not with non-smoking-related cancers (HR: 1.05 and 0.97). The associations were more evident for fiber from cereals and vegetables than from fruit. The associations were similar across BMI and physical activity categories but were stronger in smokers and participants who consumed >18 g alcohol/d. CONCLUSIONS: Higher fiber intake is associated with lower mortality, particularly from circulatory, digestive, and non-CVD noncancer inflammatory diseases. Our results support current recommendations of high dietary fiber intake for health maintenance.